PELATIHAN PENGOLAHAN DATA PENELITIAN MENGGUNAKAN APLIKASI SMART PLS (PARTIAL LEAST SQUARE) - Sahban, Muhammad Amsal; Adinugroho, Iwan; Irawan, Irawan; R, Rinovian; Khaerudin, Rizky Brehnaputrifajar; Legito, Legito (Universitas Pahlawan Tuanku Tambusai, 2024)
Pelatihan